I know how she does it : how successful women make the most of their time - Vanderkam, Laura (Portfolio/Penguin, 2017)
"Having it all" has become the subject of countless books, articles, debates, and social media commentary, with emotions running high in all directions. Many now believe this to be gospel truth: Any woman who wants to advance in a challenging career has to make huge sacrifices. She's unlikely to have a happy marriage, quality time with her kids (assuming she can have kids at all), a social life, hobbies, or even a decent night's sleep -- but what if balancing work and family is actually not as hard as it's made out to be? What if all those tragic anecdotes ignore the women who quietly but consistently do just fine with the juggle? Instead of relying on scattered stories, time management expert Laura Vanderkam set out to add hard data to the debate. She collected hour-by-hour time logs from 1,001 days in the lives of women who make at least $100,000 a year, and she found some surprising patterns in how these women spend the 168 hours that every one of us has each week. Overall, these women worked less and slept more than they assumed they did before they started tracking their time. They went jogging or to the gym, played with their children, scheduled date nights with their significant others, and had lunches with friends. They made time for the things that gave them pleasure and meaning, fitting the pieces together like tiles in a mosaic -- without adhering to overly rigid schedules that would eliminate flexibility and spontaneity. With examples from hundreds of real women, I Know How She Does It proves that women don't have to give up the things they really want.